1998
DOI: 10.1094/mpmi.1998.11.11.1069
|View full text |Cite
|
Sign up to set email alerts
|

Biocontrol by Phenazine-1-carboxamide-Producing Pseudomonas chlororaphis PCL1391 of Tomato Root Rot Caused by Fusarium oxysporum f. sp. radicis-lycopersici

Abstract: Seventy bacterial isolates from the rhizosphere of tomato were screened for antagonistic activity against the tomato foot and root rot-causing fungal pathogen Fusarium oxysporum f. sp. radicis-lycopersici. One isolate, strain PCL1391, appeared to be an efficient colonizer of tomato roots and an excellent biocontrol strain in an F. oxysporum/tomato test system. Strain PCL1391 was identified as Pseudomonas chlororaphis and further characterization showed that it produces a broad spectrum of antifungal factors (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
201
0
14

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 311 publications
(218 citation statements)
references
References 38 publications
3
201
0
14
Order By: Relevance
“…These two soils were the same as those used earlier to show the role of carbon and iron competition in soil suppressiveness to Fusarium wilts (Lemanceau et al, 1988). At this stage, the two structurally different antibiotics DAPG and phenazines were considered because of their established role in the activity of various Pseudomonas strains against pathogenic F. oxysporum (Georgakopoulos et al, 1994;Anjaiah et al, 1998;Chin-A-Woeng et al, 1998;Schouten et al, 2004) and, for DAPG-producing pseudomonads, because of their prevalence in a soil naturally suppressive to Fusarium wilt of peas (Landa et al, 2002). Molecular-based detection revealed that DAPGand phenazine-producing pseudomonads were present in the rhizosphere of flax and tomato plants grown in the wilt-suppressive soil.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These two soils were the same as those used earlier to show the role of carbon and iron competition in soil suppressiveness to Fusarium wilts (Lemanceau et al, 1988). At this stage, the two structurally different antibiotics DAPG and phenazines were considered because of their established role in the activity of various Pseudomonas strains against pathogenic F. oxysporum (Georgakopoulos et al, 1994;Anjaiah et al, 1998;Chin-A-Woeng et al, 1998;Schouten et al, 2004) and, for DAPG-producing pseudomonads, because of their prevalence in a soil naturally suppressive to Fusarium wilt of peas (Landa et al, 2002). Molecular-based detection revealed that DAPGand phenazine-producing pseudomonads were present in the rhizosphere of flax and tomato plants grown in the wilt-suppressive soil.…”
Section: Discussionmentioning
confidence: 99%
“…For example, phenazine antibiotics were shown to play a key role in the biocontrol activity of several Pseudomonas species against F. oxysporum on diverse crops (Anjaiah et al, 1998;Chin-A-Woeng et al, 1998. Also the antibiotic 2,4-diacetylphloroglucinol (DAPG) has substantial activity against pathogenic F. oxysporum (Schouten et al, 2004), and populations of DAPG-producing pseudomonads were highly enriched in a soil naturally suppressive to Fusarium wilt of peas (Landa et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In confrontation assays on solid media, including when precultures on cellophane membranes were used, A. piechaudii, P. chlororaphis and S. griseus inhibited both mycelial growth and conidial germination of H. solani, suggesting that antibiosis is a contributor to the antagonistic effect of these bacteria through the diffusion of antifungal compounds into the medium. Alcaligenes piechaudii, P. chlororaphis and S. griseus had previously been shown to produce antibiotics (Assis et al 1998;Chin-A-Woeng et al 1998;Huddleston et al 1997), though not against H. solani.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed phenazine-1-carboxamide (PCN) of Pseudomonas chlororaphis inhibits the growth of the fungal agent of tomato foot and root rot, Fusarium oxysporum f. sp. radicis lycopersici (Chin-A- Woeng et al, 1998). The phenazine pyocyanin produced by Pseudomonas aeruginosa is suggested to be involved in lung infection of cystic fibrosis patients (Caldwell et al, 2009).…”
Section: Introductionmentioning
confidence: 99%